Upaya Peningkatan Sikap Remaja dalam Pencegahan Gastritis Melalui Edukasi Kesehatan Pengaturan Pola Makan Yang Sehat - Siwi, Adiratna Sekar; Sumarni, Tri; Hidayat, Arif Imam (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Gastritis is one of the inflammations in the gastric mucosa due to a lack of attention to one's health. The prevalence of this condition in Indonesia reaches 40.8%. Gastritis occurrences are typically caused by two risk factors: uncontrollable factors such as family history, gender, and age, and controllable factors including smoking habits, the use of aspirin or nonsteroidal anti-inflammatory drugs, and irregular eating patterns. Many cases of gastritis result from irregular eating habits, including the consumption of unhealthy foods and beverages, medications, bacterial infections, and stress.Other risk factors for gastritis include the consumption of aspirin or nonsteroidal anti-inflammatory drugs, Helicobacter pylori infection, irregular meal times, stress, alcohol consumption, intake of spicy foods, and overeating. Regular eating patterns involve the quantity, frequency, and types of food intake. Irregular eating habits can lead to increased stomach acid, contributing to conditions such as pickles, vinegar, and chili sauce, resulting in an increased number of people suffering from gastric diseases.The aim of this community service activity is to enhance knowledge about gastritis and promote healthy eating habits. The educational activities include lectures using audiovisual media, question-and-answer discussions, and the completion of questionnaires related to dietary assessments and gastritis symptoms. This activity took place on June 28, 2023, targeting 23 students from the Red Cross Youth (PMR) organization at SMA Negeri 3 Purwokerto. The results indicate that the average age of respondents is 16 years, with the youngest being 15 years old and the oldest 17 years old, categorizing the respondents as mid-adolescents (15-18 years). The majority of respondents are female, accounting for 87%, with 61% exhibiting unhealthy eating patterns, and 57% showing no symptoms of gastritis. The implementation of this activity aims to empower students to control their eating patterns and other factors contributing to gastritis.